Developing an interface for bus drivers: Simplifying complexity through usability and user experience - Jönsson, Rebecka; Nilsson, Markus (My University, 2019)
Abstract The aim of this project was to facilitate Swedish public transport bus drivers’ daily work tasks by developing an interface with relevant functionality, good usability and good user experience. The project was based upon user-centered design. Interviews, observations and usability tests were conducted together with drivers. It was found in the user studies that the current solutions do not consider the complexity of the drivers’ work tasks. The currently used technology is either too utilitarian or too complex. Based upon the gathered data, a solution called MobiLity was developed. MobiLity improves the usability and user experience through presenting information in a simpler way, suggesting actions and connecting different systems. An interactive prototype of MobiLity was evaluated in user tests, where it received positive feedback. The drivers liked the simple design and found that receiving suggestions of actions was efficient and would be useful in their daily work. The conclusions made during this project was that the functionalities that bus drivers need are complex, which makes good usability even more vital. Humans still need to take the final decision in the system, as the traffic environment is complex and dynamic. Lastly, a solution based on user-centered design stand out from currently available solutions both in terms of usability and functionality.